Low-Concentration Ciprofloxacin Selects Plasmid-Mediated Quinolone Resistance Encoding Genes and Affects Bacterial Taxa in Soil Containing Manure - Huang, Ting; Xu, Ying; Zeng, Jie; Zhao, Dong-Hao; Li, Liang; Liao, Xiao-Ping; Liu, Ya-Hong; Sun, Jian (Frontiers in Microbiology, 2016)
The spread of antimicrobial resistance in environment is promoted at least in part by the inappropriate use of antibiotics in animals and humans. The present study was designed to investigate the impact of different concentrations of ciprofloxacin in soil containing manure on the development of plasmid-mediated quinolone resistance (PMQR) - encoding genes and the abundance of soil bacterial communities. For these studies, high-throughput next-generation sequencing of 16S rRNA, real-time PCR and standard microbiologic culture methods were utilized. We demonstrated that the dissipate rate of relative abundances of some of PMQR-encoding genes, such as qnrS, oqxA and aac(6’)-Ib-cr, were significantly lower with ciprofloxacin 0.04 and 0.4 mg/kg exposure as compared to no-ciprofloxacin control and ciprofloxacin 4 mg/kg exposure during two month. Also, the number of ciprofloxacin resistant bacteria was significantly greater in ciprofloxacin 0.04 and 0.4 mg/kg exposure as compared with no-ciprofloxacin control and the ciprofloxacin 4 mg/kg exposure. In addition, lower ciprofloxacin concentration provided a selective advantage for the populations of Xanthomonadales and Bacillales in orders while Agrobacterium, Bacillus, Enterococcus and Burkholderia in genera. These findings suggest that lower concentration of ciprofloxacin resulted in a slower rate of PMQR- encoding genes dissipation and selected development of ciprofloxacin-resistant bacteria in soil amended with manure.